The woodchipper - Ollmann, Joe, 1966- (Drawn and Quarterly, 2026)
"Everybody's just doing their best, trying to get through the day--why is disaster always lurking around the corner? Joe Ollmann, cartoonist of the groundbreaking Governor General Award finalist Fictional Father, returns with a suite of stories focuse don his trademark nervous wreck characters caught in a series of escalating personal disasters. What happens when a bookstore clerk gets trapped in the bathroom at work during Christmas? Or when a long-time city worker sees his hapless young colleague almost get chewed up in the titular wood chipper? In Ollmann's world, nobody can catch a break"--